Self Employment and OHS Protection - Mędrala, Małgorzata (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The article deals with the topic of self-employment in the context of the guarantees in force in Poland in the field of occupational health and safety. The Author analyzes the current regulations of the Polish Labour Code in this respect from the perspective of the self-employed and indicates their shortcomings. She also formulates de lege ferenda postulates in order to propose a model approach to the right to safe and hygienic working conditions for dependent self-employed workers. She recognizes the legitimacy of differentiating the right to health and safety for the self-employed and the employees in terms of individual benefits.